2012
DOI: 10.1073/pnas.1208603109
|View full text |Cite
|
Sign up to set email alerts
|

Independent evaluation of conflicting microspherule results from different investigations of the Younger Dryas impact hypothesis

Abstract: Firestone et al. sampled sedimentary sequences at many sites across North America, Europe, and Asia [Firestone RB, et al. (2007) Proc Natl Acad Sci USA 106:16016–16021]. In sediments dated to the Younger Dryas onset or Boundary (YDB) approximately 12,900 calendar years ago, Firestone et al. reported discovery of markers, including nanodiamonds, aciniform soot, high-temperature melt-glass, and magnetic microspherules attributed to cosmic impacts/airbursts. The microspherules were explain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

13
92
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(108 citation statements)
references
References 42 publications
13
92
0
Order By: Relevance
“…Also, in a Greenland ice core, Petaev et al (2013) found a large YDB abundance peak in the platinumgroup element platinum. Surovell et al (2009) found no YDB peaks in magnetic spherules, whereas LeCompte et al (2012) found large, welldefined YDB spherule peaks at sites common to the study by Surovell et al Also, critical overviews of the YDB hypothesis are presented in Pinter et al (2011) and Boslough et al (2012).…”
Section: Introductionmentioning
confidence: 99%
“…Also, in a Greenland ice core, Petaev et al (2013) found a large YDB abundance peak in the platinumgroup element platinum. Surovell et al (2009) found no YDB peaks in magnetic spherules, whereas LeCompte et al (2012) found large, welldefined YDB spherule peaks at sites common to the study by Surovell et al Also, critical overviews of the YDB hypothesis are presented in Pinter et al (2011) and Boslough et al (2012).…”
Section: Introductionmentioning
confidence: 99%
“…2, p. 16021), the earliest archaeologically well-documented group occupying the continent. First introduced in a popular book in 2006 (1) and soon thereafter to the scientific community (2), YDIH proponents have offered geological and geochemical evidence of an extraterrestrial impact from localities in and outside of North America (3)(4)(5)(6)(7)(8)(9)(10)(11). Independent investigators have provided support as well (12,13).…”
mentioning
confidence: 99%
“…We systematically examined the chronologies of the supposed YDB layer at the 29 sites asserted in multiple sources (2,3,(5)(6)(7)(8)(9)(10)(11) to have evidence of a cosmic impact; our efforts included crosschecking original sources used by YDIH proponents. We find that the supposed YDB layer dates to the onset of the Younger Dryas at only 3 of those 29 sites.…”
mentioning
confidence: 99%
“…However, other research questions the evidence of an impact, focussing on perceived errors in the dating of the YD boundary layer (Holliday, 2015;Meltzer et al, 2014), the misidentification of terrestrially derived carbon spherules, shocked quartz, and nanodiamonds as extraterrestrial (Pinter et al, 2011;van Hoesel et al, 2015;Tian et al, 2011), the non-uniqueness of YD nanodiamond evidence , and inconsistencies regarding the physics of bolide trajectories and impacts (Boslough et al, 2013). Despite these criticisms, independent researchers have linked spherules found within the YD boundary layer to an impact (LeCompte et al, 2012) and have identified the source of the spherules as northeastern North America (Wu et al, 2013), not only supporting the hypothesis but also suggesting an impact site proximal to the southern margin of the Laurentide Ice Sheet (Wu et al, 2013). Most recently, Wolbach et al (2018a, b) catalogue extensive evidence of global wildfires they argue were ignited by the impact of fragments of a > 100 km diameter comet.…”
Section: Compatibility With Other Hypothesesmentioning
confidence: 99%